2014
DOI: 10.1590/1414-431x20143890
|View full text |Cite
|
Sign up to set email alerts
|

Increased immunoglobulin production in silver catfish (Rhamdia quelen) exposed to agrichemicals

Abstract: Fish vaccination has been increasingly exploited as a tool to control pathogen infection. The production of immunoglobulin following vaccination might be affected by several factors such as management procedures, water temperature, and the presence of xenobiotics. In the present study, we aimed to investigate the kinetics of immunoglobulin production in silver catfish (Rhamdia quelen) inoculated with inactivated Aeromonas hydrophila and kept at two different water temperatures (17.4±0.4° or 21.3±0.3°C). The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…During the acclimatization period (7 days) and up to the end of the experiments, fish were kept in self-cleaning tanks containing 1000L of continuously running water, protected from direct sun light, and fed a commercial pelleted feed containing 42% protein. Water conditions were within the expected values, as previously reported (Kreutz et al 2014). For inoculations and blood sampling, fish were anesthetized with clove oil (50mg/L -Sigma, Brazil).…”
Section: Methodsmentioning
confidence: 79%
“…During the acclimatization period (7 days) and up to the end of the experiments, fish were kept in self-cleaning tanks containing 1000L of continuously running water, protected from direct sun light, and fed a commercial pelleted feed containing 42% protein. Water conditions were within the expected values, as previously reported (Kreutz et al 2014). For inoculations and blood sampling, fish were anesthetized with clove oil (50mg/L -Sigma, Brazil).…”
Section: Methodsmentioning
confidence: 79%
“…When common carp were exposed for 7 days to a glyphosate-POEA mixture, the mRNA levels of IgM (primary antibody type in fish; Secombes and Wang 2012) were lower as compared to in controls after 24 h; IgM protein contents were also lower at every timepoint, suggesting that antibody-mediated immunity became less efficient . In contrast, Kreutz et al (2014) noted an unexpected increase in the immunoglobulin concentrations in silver catfish exposed to glyphosate and then challenged with an inactivated form of Aeromonas hydrophila. While the studies above suggested lymphocyte responses were deteriorated by exposures to glyphosate or GBHs, the surprising results from the Kreutz group indicated that more studies are needed to apprehend further the full impact of these agents on fish lymphocyte function.…”
Section: Lymphocyte Responsesmentioning
confidence: 88%
“…These biochemical perturbations are accompanied by alterations in the metabolic and oxidative pathways (Loro et al 2015; Murussi et al 2016; Lopes et al 2017; Sobjak et al 2017; Persch et al 2018; Panetto et al 2019). In addition to these, genotoxic damage (Rodrigues et al 2019), hepatotoxicity (Santos et al 2017), histopathologic damage (Antunes et al 2017), immunotoxicity (Kreutz et al 2014), and alterations related to protein expression (Rocha et al 2015; Jaramillo et al 2017) were recorded in these studies with fish. In anuran tadpoles, it was demonstrated that glyphosate at 2 mg · L a.i.…”
Section: Resultsmentioning
confidence: 94%